Respuesta :
Answer:
(-2, -3)
Step-by-step explanation:
We assume your system of equations is ...
- 2x - y = -1
- 2x -4y = 8
You can subtract the second equation from the first to get
... (2x -y) -(2x -4y) = (-1) -(8)
... 3y = -9 . . . . . collect terms
... y = -3 . . . . . . divide by 3 . . . . this is sufficient to identify the correct answer
Substituting into the first equation, we have ...
... 2x -(-3) = -1
... 2x = -4 . . . . . add -3
... x = -2 . . . . . . .divide by 2
Now, we're sure the answer is (x, y) = (-2, -3).
![Ver imagen sqdancefan](https://us-static.z-dn.net/files/dea/028e547158a42a2b3abc7335aaea08f8.jpeg)
Answer:
(-2,-3)
Step-by-step explanation:
I just took the test!
![Ver imagen saiajalenmorris](https://us-static.z-dn.net/files/d29/c662beadd47f2918c9b2d6292f7d0858.png)